PENGARUH PENCUACAAN ALAMI TERHADAP PRODUK LATEKS KARET ALAM BERPENGISI TEPUNG KULIT PISANG YANG DIPUTIHKAN DENGAN HIDROGEN PEROKSIDA - Emelya Khoesoema, Erick Kamil, Hamidah Harahap (Jurnal Teknik Kimia USU, 2012)
The effect of exposing bleached banana skin powder-filled natural rubber products to sun light and weather with variation of bleached banana skin powder filler loading. Banana skin powder was dried and bleached with hydrogen peroxide and made into disperse system. Natural rubber latex was compounded with bleached banana skin powder with filler loading of 0 to 20 phr (per hundred rubber). Natural rubber latex products, which were produced, were hung in air and exposed to sun light and weather. The degradation of bleached banana skin powder-filled natural rubber products were evaluated by calculating weight loss of samples and performing Fourier transform infrared spectroscopy (FTIR) test. Natural rubber latex lost weight after exposure to sun light and weather from 1 to 16 weeks due to photo-oxidation process.Keywords: latex, banana skin powder, biodegradation, hydrogen peroxide, weight loss